CHARACTERISTIC OF APOPTOSIS AND EXPRESSION OF GENES-RELATED APOPTOSIS (c-myc, c-erb AND c-fos ONCOGENE) IN HeLa CELL LINES AFTER EXPOSURE BY NEEM (Azadirachta indica A.Juss) - Dessy Arisanty; Zolkapli Eshak; Fauziah Othman; Asmah Rahmat; Abdah M.D. Akim; Nurmawaty -; Suhaida. M. Jalil (Jurnal Riset Kimia, 2015)
ABSTRACT